Investigation of electrohydrodynamic behaviors from open planar solution under rod-induced electrospinning. (23rd October 2017) - Wu, Dezhi; Sun, Yu; Teh, Kwok Siong; Zhu, Yuchao; Luo, Yihui; Deng, Lei; Zhao, Libo; Luo, Guoxi; Zhao, Yang; Wang, Lingyun; Sun, Daoheng
Abstract: Understanding and controlling the electrohydrodynamic (EHD) behaviors of polymer solutions are of great importance to the design and fabrication of micro/nano devices and sensors. In this work, rod-induced electrospinning (RIES) was used as a versatile technique to study and characterize the EHD behaviors of polyethylene oxide solution during the electrospinning process. In RIES, a grounded insulated rod moves back and forth several millimeters above an open bath of polymer solution subjected to high voltage to induce the formation of Taylor cones that lead to subsequent polymer jet emissions from the solution surface. Using a phase field method, we performed finite element analysis to explore the EHD behaviors of air-polymer interface in RIES process to better understand fundamentals of this process. Pertinent theories such as phase field theories and electric field theories were briefly discussed to provide relevant background to the techniques used in this work. We investigated the RIES process and the effect of the diameter of the induction rod, applied voltage and solution conductivity on the formation of the jets. The numerical results of the formation and merging process of the jets based on different experimental parameters are in good agreement with experimental observations and provide a better understanding of the RIES process to improve the throughput of nanofibers.